Một số vấn đề về thành phần và đặc điểm Sericit - Thảo, Hoàng Thị minh; Hạnh, Nguyễn Văn; Anh, Đào Duy; Lan, Nguyễn Thanh (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Some issues on composition and characteristic of sericite In Vietnam, sericite has been interested in as a potential industrial material. This study discusses some issues on composition and characteristic of sericite following with clarifying concept of “sericite” in the international nomenclature of micas and suggests a name “di-vermiculit” (in Vietnamese) for main mineral of sericite. Some characteristics of sericite and its minerals including crystal structure, chemical composition, mineral composition and typical physical properties are presented in order to provide the fundamental information for basic and application research on sericite. The research also provides mineral formular of di-vermiculite determined from Son Binh sericite (Ha Tinh, Viet Nam), Nabeyama and Iwaya sericites (Japan).